Introducing Human Resource Management. - Hook, Caroline, 1946-; Jenkins, Andrew K.; Foot, Margaret, 1949- (Harlow, England : Pearson, 2019)
'Introducing Human Resource Management' is a lively and engaging introduction to the key topics and issues surrounding people management. Clearly linking HR theory to the work environment, this book explores core areas such as HR strategy and planning, employee engagement, diversity and equality, and talent management and development. The text combines solid academic underpinning with practical examples to allow you to consolidate your learning and apply it in practice.
Previous edition: published as by Margaret Foot, Caroline Hook, Andrew Jenkins. 2016.
Includes bibliographical references and index.
Keywords: Personnel management; Business and Management